2017
DOI: 10.1186/s12889-017-4471-9
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of the metabolic syndrome in Portugal: the PORMETS study

Abstract: BackgroundThe PORMETS study was designed to estimate the prevalence of metabolic syndrome and its determinants in the overall and administrative regions of the Portuguese mainland.MethodsA cross-sectional study of a representative sample of non-institutionalized Portuguese adults selected from primary health care centres lists including 1695 men and 2309 women was conducted from February 2007 to July 2009. A structured questionnaire was administered, collecting information on personal medical history and socio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
43
0
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(60 citation statements)
references
References 36 publications
10
43
0
7
Order By: Relevance
“…Similar to the findings of previous research, this study reported significant links between MetS and increased body weight (Ching et al 2018;Moreira et al 2014;Ortiz-Rodríguez et al 2017), waist circumference (Johari and Shahar 2014;Ortiz-Rodríguez et al 2017;Raposo et al 2017), body fat percentage (Johari and Shahar 2014;Ortiz-Rodríguez et al 2017) and BMI (Wu et al 2018). However, we did not find a significant difference across MetS status in any specific sociodemographic profile, total cholesterol level or LDL-c level.…”
Section: Contrarilysupporting
confidence: 90%
“…Similar to the findings of previous research, this study reported significant links between MetS and increased body weight (Ching et al 2018;Moreira et al 2014;Ortiz-Rodríguez et al 2017), waist circumference (Johari and Shahar 2014;Ortiz-Rodríguez et al 2017;Raposo et al 2017), body fat percentage (Johari and Shahar 2014;Ortiz-Rodríguez et al 2017) and BMI (Wu et al 2018). However, we did not find a significant difference across MetS status in any specific sociodemographic profile, total cholesterol level or LDL-c level.…”
Section: Contrarilysupporting
confidence: 90%
“…Organizations such as the National Heart, Lung, and Blood Institute (NHLBI), the American Heart Association (AHA), the World Health Organization (WHO), the National Cholesterol Education Adult Treatment (NCEP-ATP III), and the International Diabetes Federation (IDF) have proposed diverse diagnostic criteria and cut-off values for MetS [ 3 , 4 , 5 ]. Depending on the difference in the diagnostic criteria used, the incidence of metabolic syndrome in adults in varied populations has been reported to range from 28 to 50% [ 6 , 7 , 8 , 9 , 10 ]. Turkey, whose adult obesity prevalence is 28.8%, is in the top ten of the adult obesity prevalence ranking in Organization for Economic Cooperation and Development (OECD) countries [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Given that there are still several definitions in use, which differ in their cut-off values for MetS components, the prevalence of MetS in the literature ranges anywhere between 10% and 84%, depending both on the characteristics of the sample and definition used [2]. A majority of the studies indicate that 15% to 40% of the adult population in most countries can be characterized as having MetS [3][4][5][6][7]. Mediterranean countries also exhibit high MetS prevalence, ranging from one quarter to one third of the population [8][9][10].…”
Section: Introductionmentioning
confidence: 99%